High incidence of Escherichia coli resistance to colistin from chicken farms in Kathmandu Valley - Kipa Tamrakar; Avina Lama; Binita Dhakal; Luna Adhikari; Megha Shrestha; Jeena Amatya (Nepal Journal of Biotechnology)
Overusing antimicrobial growth promoters in poultry farming plays a significant role in spreading drug-resistant Escherichia coli. The widespread practice of colistin for any purpose in chickens can potentially disseminate resistant genes from the environment to humans, posing an undeniable threat to livestock and public health. In Nepal, few reports describe the incidence of E. coli bacteria, which are resistant to colistin. Henceforth, this study's purpose was evaluation of colistin-resistant E. coli from ten chicken farms (commercial and backyard) in Kathmandu Valley. In total 43 E. coli isolates were obtained from fifty chickens. All isolates were resistant to colistin, as detected by their growth on MacConkey Agar containing 4 µg/ml colistin. Antibiotic susceptibility tests were used to define the isolates further. 70.0% of isolates were categorized as multidrug-resistant, while the colistin-resistant isolates showed low resistance to Imipenem. The questionnaire data showed the rampant colistin administration in chicken feed, which may have contributed to the proliferation of E. coli isolates resistant to antibiotics in the valley. These findings highlight the importance of advanced investigation into commercial and backyard livestock to facilitate safe poultry practices.